A importância das matrizes e transformações lineares na computação gráfica - Gonçalves, Haniel Soares (2013)
Linear algebra and in particular the theory of matrices and the theory of linear transformations are areas of mathematics that can be applied not only within the mathematics, but also in many other areas of human knowledge, such as physics, chemistry, biology, all engineering, computing, economics, etc... We present examples through the importance of the matrices and linear transformations in the theory of graphic computation.